Water productivity using SAFER - Simple Algorithm for Evapotranspiration Retrieving in watershed - Daniel N. Coaguila; Fernando B. T. Hernandez; Antônio H. de C. Teixeira; Renato A. M. Franco; Janice F. Leivas (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The Cabeceira Comprida stream’s watershed, located in Santa Fé do Sul, São Paulo state, has great environmental importance. It is essential for supplying water to the population and generating surpluses for sewage dilution. This study aimed to evaluate the annual performance of the components of water productivity from Landsat-8 images of 2015, using the Simple Algorithm for Evapotranspiration Retrieving (SAFER), calculating the actual evapotranspiration (ETa), biomass (BIO) and water productivity (WP). The annual averages of ETa, BIO and WP were 1.03 mm day-1, 36.04 kg ha-1 day-1 and 3.19 kg m-3, respectively. The average annual values of ETa for land use and occupation were 1.40, 1.23, 1.05, 0.97 and 1.08 mm day-1 for the remaining forest (RF), invasive species (IS), pasture (Pa), annual crop (AC) and perennial crop (PC), respectively, with BIO of 57.64, 46.10, 36.78, 32.69, 40.03 kg ha-1 day-1 for RF, IS, Pa, AC and PC, respectively, resulting in WP of 3.94, 3.59, 3.25, 3.09, 3.35 kg m-3 for RF, IS, Pa, AC and PC, respectively. The ETa, BIO and WP adjust to the seasonality of the region, and RF and IS stood out with the highest values.